Towards a better global economy : policy implications for citizens worldwide in the 21st century - Allen, Franklin [et al] (Oxford University Press OxfordGB, 2014)
Identifies the longer-term implications for average citizens worldwide and the related policy options of major developments in the global economy.Aims to identify policies that both support global economic growth and enhance the welfare of the world's citizens, regardless of their national origin, ethnicity, race, gender, or age. Seeks to do so by fostering global cooperation and where possible and sensible, the harmonisation of policies on monetary and fiscal issues; and trade and movement of labour, capital and technology; health, education, and population; and the environment.